Seismic performance of controlled outrigger rocking wall system with different energy dissipation devices. Issue 155 (April 2022) - Yang, T.Y.; Qiao, T.; Tobber, L.; Rodgers, G.W.
Abstract: Controlled outrigger rocking wall (CORW) system is a novel earthquake resilient structural system that combines a reinforced concrete wall with an outrigger and a controlled rocking base. At the ends of the outrigger and the wall base, different dampers are used to dissipate earthquake energy. In this paper, a prototype 100 m, CORW building, is designed using the novel equivalent energy design procedure (EEDP). EEDP allows engineers to design the CORW to achieve different performance objectives at different levels of earthquake shaking intensities. The design of the CORW using dampers with different hysteretic behavior is presented in this paper. In addition, detailed numerical models for the CORW system were developed, and the seismic performance of the prototype CORW system with different dampers was systematically compared using nonlinear dynamic analyses. The result shows that the CORW can be efficiently designed using EEDP, and the desired performance of the CORW can be achieved using dampers with different hysteresis behavior. Hence, this paper demonstrates that CORW can be used as an efficient alternative seismic force resisting system for high-rise applications. Highlights: Controlled rocking outriggered wall (CORW) has high seismic performance. CORW is efficiently designed using EEDP. CORW can be designed using different combinations of damper hysteresis.